PERAN NOTARIS, PPAT, DAN BANK DALAM PENDAFTARAN HAK TANGGUNGAN ELEKTRONIK ATAS KREDIT MODAL USAHA - Pangesti, Shinta; Yovieta, Aprillia (Collegium Studiosum Journal, 2024)
In fact, the registration of mortgage rights after the implementation of business capital credit is an important stage. From the credit agreement to the registration of mortgage rights, it is inseparable from the role of a Notary, PPAT, and Bank. Because electronic deletion of mortgage rights has been implemented, it is also necessary to understand the differences between manual and electronic deletion of mortgage rights. This study aims to analyze the role of Notaries, PPATs, and Banks in the registration of HT-el for business capital credit and to analyze the differences between manual and electronic deletion of mortgage rights. The legal research used is normative legal research with a statutory approach. Primary data was obtained from interviews with two informants who were determined by purposive sampling, while secondary data was obtained through literature studies. In placing mortgage rights on business capital loans, the Notary, PPAT and Bank each have an important role. Starting from receiving the bank order letter to the issuance of the mortgage certificate, each holds an irreplaceable role and responsibility. Several differences were also found between manual and electronic deletion of mortgage rights, including: legal basis, method of implementation, role of PPAT, time limit, and final product.